Measurement of Striatal Dopamine Release Induced by Neuropsychological Stimulation in Positron Emission Tomography With Dual Injections of [11C]Raclopride - Ikoma, Yoko; Kimura, Yasuyuki; Yamada, Makiko; Obata, Takayuki; Suhara, Tetsuya; Ito, Hiroshi (Frontiers in Psychiatry, 2022)
Objectives: Positron emission tomography (PET) with [11C]raclopride has been applied to measure changes in the concentration of endogenous dopamine induced by pharmacological challenge or neuropsychological stimulation by evaluating the binding potential (BP) between the baseline and activated state. Recently, to reliably estimate BP in the activated state, a new approach with dual-bolus injections in a single PET scan was developed. In this study, we investigated the feasibility of applying this dual-bolus injection approach to measure changes in endogenous dopamine levels induced by cognitive tasks in humans. Methods: First, the reproducibility of BP estimation using the dual-bolus injection approach was evaluated using PET scans without stimulation in nine healthy volunteers. A 90-min scan was performed with bolus injections of [11C]raclopride administered at the beginning of the scan and 45 min after the first injection. BPs in the striatum for the first injection (BP1) and second injection (BP2) were estimated using an extended simplified reference tissue model, and the mean absolute difference (MAD) between the two BPs was calculated. The MAD was also compared with the conventional bolus-plus-continuous infusion approach. Next, PET studies with a cognitive reinforcement learning task were performed on ten healthy volunteers using the dual-bolus injection approach. The BP1 at baseline and BP2 at the activated state were estimated, and the reduction in BP was evaluated. Results: In the PET scans without stimulation, the dual-bolus injection approach showed a smaller MAD (< 2%) between BP1 and BP2 than the bolus-plus-continuous infusion approach, demonstrating good reproducibility of this approach. In the PET scans with the cognitive task performance, the reduction in BP was not observed in the striatum by either approach, showing that the changes in dopamine level induced by the cognitive tasks performed in this study were not sufficient to be detected by PET. Conclusions: Our results indicate that the cognitive task-induced changes in dopamine-related systems may be complex and difficult to measure accurately using PET scans. However, the proposed dual-bolus injection approach provided reliable BP estimates with high reproducibility, suggesting that it has the potential to improve the accuracy of PET scans for measuring changes in dopamine concentrations.